2000
DOI: 10.1007/s002130000420
|View full text |Cite
|
Sign up to set email alerts
|

Acute administration of amitriptyline and mianserin increases dopamine release in the rat nucleus accumbens: possible involvement of serotonin 2C receptors

Abstract: Previous studies of conventional tricyclic and non-tricyclic antidepressants have suggested that a number of these drugs display considerable pharmacological activity at 5-HT2C receptors in the brain. There is evidence that 5-HT2C receptors are involved in the control of the activity of the central dopaminergic system. Therefore, the effects of amitriptyline (5 mg/kg and 10 mg/kg i.p.) and of the atypical antidepressant mianserin (2.5 mg/kg and 5 mg/kg i.p.) were studied on the extracellular concentration of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 41 publications
(42 reference statements)
2
22
0
Order By: Relevance
“…In the same experiment there were, however, no differences in the basal or evoked DA levels between chloral hydrate anesthetized and unanaesthetized rats [29]. Additional acute microdialysis studies examining accumbens DA have used choral hydrate as an anesthetic because it has minimal effects on mesoaccumbens DA efflux over time [30][31][32][33] and it has a long effective half life (∼6.5 h).…”
Section: Discussionmentioning
confidence: 99%
“…In the same experiment there were, however, no differences in the basal or evoked DA levels between chloral hydrate anesthetized and unanaesthetized rats [29]. Additional acute microdialysis studies examining accumbens DA have used choral hydrate as an anesthetic because it has minimal effects on mesoaccumbens DA efflux over time [30][31][32][33] and it has a long effective half life (∼6.5 h).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the 5-HT 2C agonist, Ro 60-0175, attenuates cocaine-primed reinstatement (Grottick et al, 2000), providing further evidence for a role of 5-HT 2C receptors in this behavior. SB 242,084 likely enhances cocaine-primed reinstatement by enhancing dopamine neurotransmission since previous research has shown that 5-HT 2C receptors inhibit mesocorticolimbic dopamine release , 2000a, which is thought to play a role in cocaine-primed reinstatement of cocaine-seeking behavior (Weissenborn et al, 1996;Khroyan et al, 2000;Alleweireldt et al, 2002). The reason for the discrepancy in the effects of SB 242,084 on cocaine reinstatement across studies is unclear, but may be due to differences in cocaine priming and/or SB 242,084 doses tested.…”
Section: Discussionmentioning
confidence: 99%
“…tricyclics (amitriptyline, imipramine), mianserin, nefazodone, opipramole, trazodone [67,152,153] and fluoxetine [148,154]. Based on those findings, Di Matteo and colleagues [155] have carried out experiments showing that acute administration of amitriptyline and mianserin enhances DA release in the rat nucleus accumbens by blocking 5-HT 2C receptor subtypes. However, these drugs have multiple receptor and transporter interactions and it is difficult to asses what the real contribution of the 5-HT 2C receptor blockade is to the total clinical activity of the drugs.…”
Section: -Ht 2c Recptors and Depressionmentioning
confidence: 99%